Pengaruh Tekanan Eksternal Terhadap Penggunaan Sistem Pengukuran Kinerja Untuk Tujuan Opersional Dan Dampaknya Terhadap Kinerja - Anita Primastiwi (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2016)
The aim of this study is to give empirical evidence about the influence of external pressure on the using of performance measurement system for operational purposes and the impact on the performance of public sector organizations. The samples were the SKPD’s and BUMD’s chairmen or chairwomen who lead the governmental services in Klaten Regency, and they must be in their term of office for at least one year. This study analyzed their perceptions about the statements in the questionaire. The data was analized by partial least square (PLS) with Smart PLS Version 3.0. The findings showed an empirical evidence that accountability demands from supervisors and specific (external) stakeholder groups do have positive and significant effect on the using of performance measurement system for operational purposes, but that general public or political attention does not affect to the using of performance measurement system for operational purposes. The finding also showed that using the system for operational purposes has no impact on performance.